MAKNA SIMBOLIK TARI PENGUTON DI KECAMATAN KAYUAGUNG KABUPATEN OGAN KOMERING ILIR SUMATRA SELATAN - Retna Susanti (Institut Seni Indonesia Surakarta, 2014)
The research entitled â€œThe Symbolic Meaning of the Penguton Dance in the KayuagungSub-District of the Ogan Komering Ilir District in South Sumateraâ€is intended as a form ofpreservation and a source of information about traditional dance, specifically in South Sumatera.A number of semiotic approaches are used to analyze the problems addressed in the research, inorder to investigate the facts and phenomena related to the Penguton dance in the Kayuagungsub-district of the Ogan Komering Ilir district. Based on the existing phenomena, the researchaims to discover the background to the existence of the Penguton dance, the process of developmentof the Penguton dance up to the present day, and the symbolic meaning contained in thePenguton dance. In order to find the answers to these questions, a qualitative method was usedtogether with semiotic theories, while the techniques for collecting data included observation,interviews, and a study of written data and documents. This was followed by an analysis of thedata, verification, documentation, and conclusions.Â The results of the research show that the symbolization contained in the Penguton dance isan expression of the hearts and minds of the local community as a structure for their society.Tradition refers to the habits of a community which become rules in its supporting environment.The supporting community for the Penguton dance is of a sacred nature and as such, not allmembers of the general public are able to enjoy a performance of the Penguton dance and themeaning it contains. This rule contains an understanding which becomes a strength of symbolizationand thus forms a social strata.Keywords: Penguton Dance, Meaning, Symbolic.